2019
DOI: 10.1177/1461348419874932
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic modeling and analysis for aviation axial piston pump in center spring return mechanism

Abstract: Aviation axial piston pump is an important energy conversion component in aircraft hydraulic system, and the study on the nonlinearity of key operating mechanism is very necessary for improving the reliable operation of the pump. Addressing the aviation axial piston pump, this article analyzes nonlinear dynamic characteristics of the center spring return mechanism by using theoretical analysis and numerical simulation. Firstly, mathematical models of oil-film forces of slipper/swash plate pair and cylinder/por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Through the analysis of its dynamic performance and nonlinear dynamics, it was found that the space rotating clearance has more influence on mechanism than the plane clearance. Hang et al 10 explored the nonlinear dynamics of central spring return mechanism based on Lyapunov exponential spectrum, bifurcation diagram, time series and other nonlinear theories by combining theoretical analysis with numerical simulation. Ahmed et al 11 proposed a novel nonlinearity condition that could be used for ET consensus of a series of nonlinear MASs.…”
Section: Introductionmentioning
confidence: 99%
“…Through the analysis of its dynamic performance and nonlinear dynamics, it was found that the space rotating clearance has more influence on mechanism than the plane clearance. Hang et al 10 explored the nonlinear dynamics of central spring return mechanism based on Lyapunov exponential spectrum, bifurcation diagram, time series and other nonlinear theories by combining theoretical analysis with numerical simulation. Ahmed et al 11 proposed a novel nonlinearity condition that could be used for ET consensus of a series of nonlinear MASs.…”
Section: Introductionmentioning
confidence: 99%
“…Pump controlled flowrate control: In this method, the pressure difference can be kept constant through CPDCV and variable displacement pump, so as to reduce the recirculation and throttling loss of excess fuel [7]. Nevertheless, its application is mainly limited to gas turbines because of the high cost and nonlinear characteristics [8].…”
mentioning
confidence: 99%